2018
DOI: 10.1074/jbc.ra117.000440
|View full text |Cite
|
Sign up to set email alerts
|

JNK2 up-regulates hypoxia-inducible factors and contributes to hypoxia-induced erythropoiesis and pulmonary hypertension

Abstract: The hypoxic response is a stress response triggered by low oxygen tension. Hypoxia-inducible factors (HIFs) play a prominent role in the pathobiology of hypoxia-associated conditions, including pulmonary hypertension (PH) and polycythemia. The c-Jun N-terminal protein kinase (JNK), a stress-activated protein kinase that consists of two ubiquitously expressed isoforms, JNK1 and JNK2, and a tissue-specific isoform, JNK3, has been shown to be activated by hypoxia. However, the physiological role of JNK1 and JNK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…The 40 genes differentially expressed in the heart were enriched into three GO terms (GO:0046329 ~ negative regulation of JNK cascade; GO:0016477 ~ cell migration; GO:0001046 ~ core promoter sequence-specific DNA binding). JNK (c-Jun N-terminal protein kinase) is a class of stress-activated protein kinase, and its activation induced by hypoxia is an early response to hypoxic stress [ 71 , 72 ]. It was reported that JNK2 upregulated HIFs (Hypoxia Inducible Factors) and contributed to pulmonary hypertension and polycythemia induced by hypoxia [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 40 genes differentially expressed in the heart were enriched into three GO terms (GO:0046329 ~ negative regulation of JNK cascade; GO:0016477 ~ cell migration; GO:0001046 ~ core promoter sequence-specific DNA binding). JNK (c-Jun N-terminal protein kinase) is a class of stress-activated protein kinase, and its activation induced by hypoxia is an early response to hypoxic stress [ 71 , 72 ]. It was reported that JNK2 upregulated HIFs (Hypoxia Inducible Factors) and contributed to pulmonary hypertension and polycythemia induced by hypoxia [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that deubiquitylase Cezanne (also known as OTUD7B) regulates HIF2A expression via transcription factor E2F1 that directly affects the HIF2A gene expression (21). Moreover, poly (ADP-ribose) polymerase-1 (PARP-1) and JNK2 has been reported to regulate HIF2A expression level (22,23). Also, insulin-like growth factor 2 (IGF2)-induced PI3K-mTORC2 signaling was shown to regulate HIF2A mRNA expression in neuroblastoma cells (24).…”
mentioning
confidence: 99%
“…recently reported that JNK2 may play a role in the development of hypoxia-induced PH since mice deficient in JNK2 are relatively (but not completely) spared from hypoxia-induced PH. 11 …”
Section: Discussionmentioning
confidence: 99%
“…To test our hypothesis, we evaluated whether PH pathology is associated with the activation of JNK1/2 using lung tissues from healthy humans and PH patients as well as lung tissues from a well-established bovine model of severe hypoxic PH. Since loss-of-function studies in mice have provided major insights into the function of JNK isoforms in development and disease, 11 , 15 we then used JNK1 and JNK2 null mice to evaluate further the role of each individual isoform in the molecular mechanisms driving the development and progression of PH. For that, wild-type (WT), JNK1 -/- , and JNK2 -/- mice were exposed to either room air (normoxia) or 10% O 2 (hypoxia) for six weeks to induce PH.…”
Section: Introductionmentioning
confidence: 99%